Os documentos arquivísticos digitais no sistema de informações SIE/UFSM: da produção ao acesso - Viana, Gilberto Fladimar Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research analyzes the digital and analogical archival documents in the Information System for Education, from the Federal University of Santa Maria - SIE / UFSM - applied to the subsystem Institutional Production, Project Registration Module within the Arts and Letters Center - CAL. It develops studies that propitiate the adequate treatment of documentary mass created, stored and accessed in information systems such as the SIE / UFSM, wherein the study was developed through compliance with the theoretical, normative, legal, institutional and social framework related to the management and documentary allocation of digital documents in the Institution. The research was developed through a qualitative and quantitative approach, consisting of examinations through access and consultation of the SIE in management operational level, supported by the theoretical and normative reference frame relevant to topics developed throughout the research, which is initially detailing the SIE / UFSM, the project registration module, which also carries out the quantitative analysis of projects registered in it, derived from CAL. It was observed quantitative variation of the projects situations at different times depending on the institutional setting of the maximum duration time as well as institutional actions to encourage the development of projects. Were addressed also the issues of documentary heritage and memory associated to oblivion in view of SIE / UFSM, evidencing the absence of institutional actions (policies) that recognize the potential and establish the SIE as source of institutional memory consubstantiated as documentary heritage available to society; proceeds, also, to the theoretical context of contemporary Archival Science considering the analogical and digital documents, the concept of information systems, as well as the role of the archivist in this context. It is observed that the contemporary archivist actuation reality ...

Esta pesquisa analisa os documentos arquivísticos digitais e analógicos no Sistema de Informações para o Ensino, da Universidade Federal de Santa Maria - SIE/UFSM - aplicado ao subsistema Produção Institucional, Módulo de Registro de Projetos, no âmbito do Centro de Artes e Letras - CAL. Desenvolve estudos que propiciem o adequado tratamento da massa documental criada, armazenada e acessada em sistemas de informações, como o SIE/UFSM, sendo que o estudo se desenvolveu através da observância do arcabouço teórico, normativo, legal, institucional e social, pertinente à gestão e à destinação documental dos documentos digitais na Instituição. A pesquisa foi desenvolvida através de uma abordagem quali-quanti, constituída de levantamentos através de acessos e consulta ao SIE em nível operacional gerencial, apoiada pelo referencial teórico e normativo pertinente aos tópicos desenvolvidos ao longo da pesquisa, que se constitui, inicialmente, do detalhamento do SIE/UFSM, do módulo de registro projetos, onde também se procede à análise quantitativa dos projetos nele registrados, provenientes do CAL. Foi observada a variação quantitativa das situações dos projetos em períodos distintos em função da definição institucional do tempo máximo de sua duração, assim como ações institucionais de incentivo ao desenvolvimento de projetos. Foram abordadas, também, as questões do patrimônio documental e da memória associados ao esquecimento na perspectiva do SIE/UFSM, constatando-se a ausência de ações institucionais (políticas) que reconheçam a potencialidade e estabeleçam o SIE como gênese da memória institucional consubstanciada como patrimônio documental disponível à sociedade; procede-se, também, à contextualização teórica da Arquivologia contemporânea, considerando os documentos analógicos e digitais, o conceito de sistemas de informação, assim como a atuação do arquivista...
Keywords: Direito à informação; Documentos arquivísticos; Banco de dados; Documentos; Right of free information